Patients with moderate to severe COVID-19 outcomes on remdesivir according to baseline 4C mortality score. (February 2023) - Sellers, Jacob; Chang, Jongwha; Jones, Jessica; Hintze, Trager D.
Abstract: Background: Remdesivir was the first antiviral to show clinical benefit in patients with moderate-to-severe COVID-19. Previous trials demonstrated a faster time to recovery in hospitalized patients treated with remdesivir vs placebo. Current guidelines recommend treatment with remdesivir based on hospitalization status, oxygen requirements, and time from symptom onset. However, other factors may be evaluated to determine disease severity and risk for progression. The 4C mortality score is a validated, eight variable score that may be used to categorize patients by mortality risk at the time of hospital admission for COVID pneumonia. The objective of this study was to determine if the 4C mortality score may be used to predict which patients with moderate to severe COVID-19 would benefit the most from remdesivir at the time of hospital admission. Methods: This was a single-center retrospective cohort study comparing time to recovery among hospitalized patients with moderate-to-severe COVID-19 who were treated with remdesivir compared to those who were treated with standard of care (SOC). The primary outcome was time to recovery, defined as discharge from the hospital or no longer requiring supplemental oxygen, stratified by the 4C mortality score risk group. Secondary outcomes included in-hospital mortality, hospital length of stay, and time to recovery in patients who were started on remdesivir within 7 days from symptom onset vs after 7 days from symptom onset. A survival analysis was used to analyze time to recovery outcomes. Results: Data was collected and analyzed for a total of 300 patients, of which 200 received remdesivir and 100 received SOC. Patients in the remdesivir group had a longer time to recovery compared to patients in the SOC group (6 days vs 4 days). This finding was driven by patients who were categorized to the intermediate risk and high risk mortality groups. Additionally, patients who received remdesivir had a longer length of hospital stay compared to those who received SOC (12 days vs 9 days). Remdesivir was not associated with an increased rate of adverse events. Conclusions: This study of patients admitted with moderate-to-severe COVID-19 found that patients who were treated with remdesivir had a longer time to recovery and a longer length of stay compared to those who received SOC. These findings add to the body of evidence questioning the benefit of remdesivir therapy among patients hospitalized with COVID-19.